2017
DOI: 10.3390/ijerph14030298
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Health Co-Benefits in Relation to Greenhouse Gas Emission Reductions: A Survey among Urban Residents in Three Chinese Cities

Abstract: Limited information is available on the perceptions of stakeholders concerning the health co-benefits of greenhouse gas (GHG) emission reductions. The purpose of this study was to investigate the perceptions of urban residents on the health co-benefits involving GHG abatement and related influencing factors in three cities in China. Beijing, Ningbo and Guangzhou were selected for this survey. Participants were recruited from randomly chosen committees, following quotas for gender and age in proportion to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Cities now house more than half of the world's population, a fraction that is growing rapidly, are responsible for 75% of greenhouse gas emissions, and account for 85% of global economic activity. 408,409 Cities, especially rapidly growing cities in low-income and middle-income countries, have some of the world's highest concentrations of ambient air and chemical pollution and the highest prevalence of disease caused by these forms of pollution.…”
Section: Engage With the Private Sectormentioning
confidence: 99%
“…Cities now house more than half of the world's population, a fraction that is growing rapidly, are responsible for 75% of greenhouse gas emissions, and account for 85% of global economic activity. 408,409 Cities, especially rapidly growing cities in low-income and middle-income countries, have some of the world's highest concentrations of ambient air and chemical pollution and the highest prevalence of disease caused by these forms of pollution.…”
Section: Engage With the Private Sectormentioning
confidence: 99%
“…In a metanalysis of behavioral intervention to promote individual engagement in climate mitigation actions found behavioral interventions alone were insufficient to yield long term change, but might be useful in combination with other strategies [45]. When considering how to nudge individuals towards pro-climate behaviors, be it for themselves or for the environment, behavioral economics, a field which focuses on understanding individual decision making, has suggested that both the framing and the emotional content of the messages can be important [74]. Framing climate change within a public health focus has been suggested as a means to engage policy makers, namely to account for the co-benefits of GHG emission reductions [75].…”
Section: Plos Climatementioning
confidence: 99%
“…Pertubuhan Kesihatan Sedunia (WHO) trurut menganggarkan bahawa kira-kira 4.2 juta kes kematian pramatang individu dicatatkan di seluruh dunia akibat daripada pencemaran trafik bandar (WHO, 2018). Walaupun pelbagai kajian seluruh dunia (Elosta et al, 2013;Kamimura et al, 2017;Xu et al, 2015;Sarker et al, 2018;Deguen et al, 2017;Gao et al, 2017;Li & Tilt, 2019) yang dijalankan membuktikan bahawa penduduk setempat tahu dan cakna tentang masalah pencemaran udara yang berlaku, namun disebabkan oleh kepelbagaian dan perbezaan aspek sosioekonomi individu dan gaya hidup secara langsung mewujudkan masalah alam sekitar ini menjadi semakin serius khususnya kepada kesihatan manusia. Oleh itu, berdasarkan beberapa kajian tersebut mengesahkan bahawa masalah pencemaran udara di bandar utama mempunyai hubungan yang kuat dengan pengetahuan serta kesedaran individu tentang masalah pencemaran udara trafik yang berlaku.…”
Section: Pengenalanunclassified